FEATURES OF THE CREATION OF TRAINING CONTENT, TAKING INTO ACCOUNT THE DYNAMIC DEVELOPMENT OF THE FIELD OF COMPUTER SCIENCE - Nurbekova, Ж.К.; Uzakova, А.К. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
The field of informatics is developing rapidly, therefore, for the effectiveness of the learning process, it is important to ensure the quality of the learning content in a timely manner. The rapid change of information, the updating of technologies requires a dynamic change in the content of education. The article presents the features of creating the content of computer science in accordance with the dynamic development of the subject area of computer science: sections that need to be included in the content of education, the formation of research skills among students as a result of constructivist activity. These features are critical to ensuring that computer science students have the skills they need to succeed in this ever-changing field. This research was conducted by the Republican Scientific and Practical Center for Educational Content Expertise together with the National Academy of Education named after Y. Altynsarin of the Ministry of Education of the Republic of Kazakhstan as part of the program-targeted financing of the research OR 11465474 "Scientific foundations of modernization of the education system and science".